2012
DOI: 10.2224/sbp.2012.40.4.699
|View full text |Cite
|
Sign up to set email alerts
|

Sport Participation and Self-Esteem as Mediated by Perceived Peer Acceptance and Sport Self-Concept in Taiwanese College Students

Abstract: In this study we posited that sport participation would be positively associated with self-esteem through the mediating variables of perceived peer acceptance and sport self-concept. A survey was completed by 489 Taiwanese college students using a 2-stage sampling design and structural equation modeling revealed that sport participation positively predicts peer acceptance and sport self-concept. Additionally, peer acceptance and sport self-concept were found to positively predict self-esteem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
3
6
0
Order By: Relevance
“…In this study, we examined that influence of sports/health activities and also analyzed how happiness changed, depending on self-esteem. According to this study, sports/health activities were associated with higher positive self-esteem and lower negative self-esteem, a finding that is consistent with those of previous research [3] [4] [5] [7]. It means that students who participated in sports/health activities had lower levels of negative self-esteem than did their peers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we examined that influence of sports/health activities and also analyzed how happiness changed, depending on self-esteem. According to this study, sports/health activities were associated with higher positive self-esteem and lower negative self-esteem, a finding that is consistent with those of previous research [3] [4] [5] [7]. It means that students who participated in sports/health activities had lower levels of negative self-esteem than did their peers.…”
Section: Discussionsupporting
confidence: 91%
“…The focus of much research indicated that the participation of sports or physical activity is positively associated with self-esteem. For example, they have investigated a variety of variables proposed to mediate the relationship between sports participation and individual's self-esteem [7] [8] [9] [10] [11]. In this context Liu, Wu and Ming (2015) found that intervention of physical activity is associated with increased self-concept and self-worth in children and adolescents [12].…”
Section: Introductionmentioning
confidence: 99%
“…Participation in physical activity brings people together and provides personal identity, social identity, and a sense of group membership; it also facilitates communication between people and communities without race, gender, culture and age discrimination (Yıldıran & Yetim, 1996). Participation in physical activity has positive effects on self-respect (Chen et al, 2012;Joseph et al, 2014;Yiğitler, 2014), psychological well-being (Edwards, 2006;Garcia et al, 2012;Verner et al, 2017;Wiese et al, 2018), physical and mental health (Cho & Cho, 2011;Park et al, 2017;Ostovarfar et al, 2018;Way et al, 2018); however, the number of people who do not participate in physical activity is quite high worldwide (World Health Organization, 2004). For example, Bauman (2009) collected data from about 53 thousand people across 20 countries and reported that New Zealand, Czech Republic, the USA, Canada and Australia are the countries where participation in physical activity is most prevalent, while the levels of physical activity are remarkably quite low in the remaining countries.…”
Section: Introductionmentioning
confidence: 99%
“…Peer acceptance has been linked with self-worth and self esteem in girls (Klima & Repetti, 2003;Walker & Greene, 1986). In addition, previous research has found peer acceptance to mediate the association between sport participation and self-esteem (Chen, Chen, Lin, & Chen, 2012;Daniels & Leaper, 2006). Such studies have tended to evaluate peer acceptance from a more general perspective.…”
Section: Team Acceptance Win Orientation and Self-esteemmentioning
confidence: 99%